2008
DOI: 10.1186/1747-597x-3-20
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of alcohol dependence in patients with co-morbid major depressive disorder – predictors for the outcomes with memantine and escitalopram medication

Abstract: Background: Alcohol dependence comorbid with major depressive disorder poses a major challenge in the clinical setting. The results in the treatment with selective serotonin re-uptake inhibitors have been conflicting. Thus, we compared in alcohol-dependent patients with co-morbid major depressive disorder the selective serotonin re-uptake inhibitor escitalopram to a compound that acts on different transporter system and may reduce craving, the glutamate receptor antagonist memantine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…Subsequently, a case report explored the antidepressant efficacy of repeat-dose ketamine followed by memantine; although this patient was eventually on seven psychotropic medications, she remained in remission for at least 13 weeks (124). Echoing the previous link between NMDA receptor antagonists and ketamine response, another randomized, non-placebo-controlled trial of memantine (20 mg/day) versus escitalopram (20 mg/day) in patients with MDD comorbid with alcohol dependence found that memantine had antidepressant and anxiolytic effects, improved psychosocial functioning, and decreased alcohol consumption (125, 126). …”
Section: Other Nmda Receptor Antagonistsmentioning
confidence: 99%
“…Subsequently, a case report explored the antidepressant efficacy of repeat-dose ketamine followed by memantine; although this patient was eventually on seven psychotropic medications, she remained in remission for at least 13 weeks (124). Echoing the previous link between NMDA receptor antagonists and ketamine response, another randomized, non-placebo-controlled trial of memantine (20 mg/day) versus escitalopram (20 mg/day) in patients with MDD comorbid with alcohol dependence found that memantine had antidepressant and anxiolytic effects, improved psychosocial functioning, and decreased alcohol consumption (125, 126). …”
Section: Other Nmda Receptor Antagonistsmentioning
confidence: 99%
“…Subsequently, a case report explored the antidepressant efficacy of repeat-dose ketamine followed by memantine; although this patient was eventually on many psychotropic medications, she remained in remission for at least approximately 3 months on memantine (Kollmar et al 2008). Another randomized, non-placebo-controlled trial of memantine (20 mg/day) versus escitalopram (20 mg/day) in patients with MDD comorbid with alcohol dependence found that memantine had antidepressant and anxiolytic effects, improved psychosocial functioning, and decreased alcohol consumption (Muhonen et al 2008a, b). …”
Section: Glutamatergic Medications In the Treatment Of Major Depressimentioning
confidence: 99%
“…Therefore, the use of antidepressants as adjunctive therapy for AUD with comorbid depression might be considered since combining acamprosate and SSRIs such as escitalopram in theory could simultaneously downregulate glutamatergic and upregulate serotonergic neurotransmissions, in turn suppressing ethanol consumption. Clinical studies found SSRIs improved depressed mood and decrease alcohol use in some alcohol dependent individuals (Kranzler et al, 2012; Muhonen et al, 2011; Muhonen et al, 2008). Escitalopram is currently the most widely used SSRI (Owens et al, 2001).…”
Section: Introductionmentioning
confidence: 99%